Distribution of depression, somatization and pain-related impairment in patients with chronic temporomandibular disorders - Giancarlo De La Torre Canales; Luca Guarda-Nardini; Célia Marisa Rizzatti-Barbosa; Paulo César Rodrigues Conti; Daniele Manfredini (University of São Paulo, 2019)
Abstract Objective the aim of this study was to describe the frequency of psychosocial diagnoses in a large sample of patients attending a tertiary clinic for treatment of temporomandibular disorders (TMD). Material and Methods six hundred and ninety-one patients who sought treatment for pain-related TMD were selected. Chronic pain-related disability (Graded Chronic Pain Scale, GCPS), depression [Symptoms Checklist-90 (SCL-90) scale for depression, DEP] and somatization levels (SCL-90 scale for non-specific physical symptoms, SOM) were evaluated through the Research Diagnostic Criteria for TMD (RDC/TMD) Axis II psychosocial assessment; TMD diagnoses were based on the Axis I criteria. Results the majority of patients presented a low disability or no disability at all, with only a small portion of individuals showing a severely limiting, high disability pain-related impairment (4.3%). On the other hand, abnormal scores of depression and somatization were high, with almost half of the individuals having moderate-to-severe levels of depression and three-fourths presenting moderate-to-severe levels of somatization. The prevalence of high pain-related disability (GCPS grades III or IV), severe/moderate depression and somatization was 14.3%, 44% and 74.1% respectively. Gender differences in scores of SCL-DEP (p=0.031) and SCL-SOM (p=0.001) scales were signficant, with females presenting the highest percentage of abnormal values. Conclusion patients with TMD frequently present an emotional profile with low disability, high intensity pain-related impairment, and high to moderate levels of somatization and depression. Therefore, given the importance of psychosocial issues at the prognostic level, it is recommended that clinical trials on TMD treatment include an evaluation of patients' psychosocial profiles.